A global synthesis of the rate and temperature sensitivity of soil nitrogen mineralization: latitudinal patterns and mechanisms. (25th June 2016) - Liu, Yuan; Wang, Changhui; He, Nianpeng; Wen, Xuefa; Gao, Yang; Li, Shenggong; Niu, Shuli; Butterbach‐Bahl, Klaus; Luo, Yiqi; Yu, Guirui
Abstract: Soil net nitrogen (N) mineralization (Nmin ) is a pivotal process in the global N cycle regulating the N availability of plant growth. Understanding the spatial patterns of Nmin, its temperature sensitivity ( Q 10 ) and regulatory mechanisms is critical for improving the management of soil nutrients. In this study, we evaluated 379 peer‐reviewed scientific papers to explore how Nmin and the Q 10 of Nmin varied among different ecosystems and regions at the global scale. The results showed that Nmin varied significantly among different ecosystems with a global average of 2.41 mg N soil kg −1 day −1 . Furthermore, Nmin significantly decreased with increasing latitude and altitude. The Q 10 varied significantly among different ecosystems with a global average of 2.21, ranging from the highest found in forest soils (2.43) and the lowest found for grassland soils (1.67) and significantly increased with increasing latitude. Path analyses indicated that Nmin was primarily affected by the content of soil organic carbon (C), soil C:N ratio, and clay content, where Q 10 was primarily influenced by the soil C:N ratio and soil pH. Furthermore, the activation energy ( E a ) of soil N mineralization was significantly and negative correlated with the substrate quality index among all ecosystems, indicating the applicability of the carbon quality temperature hypothesis to soil N mineralization at a global scale. These findings provided empirical evidence supporting that soil N availability, under global warming scenarios, is expected to increase stronger in colder regions as compared with that low‐latitude regions due to the higher Q 10 . This may alleviate the restriction of N supply for increased primary productivity at higher latitudes.